2010
DOI: 10.1111/j.1755-3768.2010.02030.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative vitreous IL‐8 and VEGF levels with visual acuity after vitrectomy in proliferative diabetic retinopathy

Abstract: Acta Ophthalmol. 2010: 88: e311–e316 Abstract. Purpose:  To determine whether the vitreous levels of interleukin 8 (IL‐8) and vascular endothelial growth factor (VEGF) of patients with proliferative diabetic retinopathy (PDR) were associated with poor visual acuity after vitrectomy. Methods:  Observational cross‐sectional study. Patient clinical characteristics and preoperative eye characteristics (63 eyes): visual acuity, iris neovascularization, vitreous haemorrhage, macular detachment, macular oedema, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
0
29
2
Order By: Relevance
“…Indeed, we did not identify preoperative factors predictive of the visual outcomes in this study, although several ocular and systemic prognostic factors have been reported [38][39][40][41]. We did show for the first time the clinical relevance of a disrupted ellipsoid zone or ELM on SD-OCT images after MIVS for vitreous hemorrhage due to PDR, suggesting the potential utility of SD-OCT examination after surgery.…”
Section: Discussioncontrasting
confidence: 71%
“…Indeed, we did not identify preoperative factors predictive of the visual outcomes in this study, although several ocular and systemic prognostic factors have been reported [38][39][40][41]. We did show for the first time the clinical relevance of a disrupted ellipsoid zone or ELM on SD-OCT images after MIVS for vitreous hemorrhage due to PDR, suggesting the potential utility of SD-OCT examination after surgery.…”
Section: Discussioncontrasting
confidence: 71%
“…34 VEGF was found elevated in the vitreous of our patients with PDR, which is in accordance with previous findings. [13][14][15][16]25,26,28,34 IL6 is a multifunctional cytokine that indirectly causes an increase in vascular permeability and neovascularization by inducing the expression of VEGF, and also directly increases endothelial cell permeability in vitro by rearranging actin filaments and by changing the shape of endothelial cells. 35 Serum and vitreous levels of IL-6 may have a role in PDR.…”
Section: Current Eye Researchmentioning
confidence: 99%
“…Interleukins play an important role in the regulation of immune mechanisms. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] ABSTRACT Objective: Inflammatory reaction has been shown to involve the progress of type 2 (non-insulin-dependent) diabetes. We, therefore, examined the effects of inflammatory cytokines and angiogenic factors in the pathogenesis of proliferative diabetic retinopathy (PDR) in type 2 diabetes.…”
mentioning
confidence: 99%
“…have shown that the levels of IL-6, IL-8 (CXCL8), IL-10 (CXCL10), IL-13, IP-10, MCP-1(CCL2), MIP-1β (CCL4), PDGF, and VEGF in the vitreous fluid are significantly higher in any sign of a diabetic retinopathy group 53. Studies have shown that the elevated vitreous IL-8 levels in diabetic subjects are associated with deteriorating visual acuity in diabetic retinopathy 54. Elevation of the aqueous concentration of MCP-1 / CCL2, IP-10, and IL-8 levels in eyes with severe NPDR suggests that inflammatory changes precede the development of neovascularization in PDR 55.…”
Section: Inflammatory Biomarkers In Diabetic Retinopathymentioning
confidence: 99%
“…The important observation one can infer from the above set of studies are: (1) There are common sets of inflammatory cytokines that are upregulated in both serum and vitreous / aqueous samples in subjects with retinopathy, (2) the same kind of cytokines are involved in the pathogenesis of both PDR and NPDR [Table 2] and these cytokines can have multiple interactions to impact the pathogenesis of diabetic retinopathy 545559. Despite the important function of VEGF as an angiogenic and inflammatory factor, studies have observed that a selective blocking of VEGF using bevacizumab injections (anti-VEGF) has no influence on the control of other immunogenic cytokines, such as, MCP-1 and IL-6, in the aqueous humor of DME 60.…”
Section: Inflammatory Biomarkers In Diabetic Retinopathymentioning
confidence: 99%